Pay equity for New Zealand school librarians and library assistants (Synergy, 2023)
Tuohy and Eastland describe the journey of the New Zealand Librarians and LibraryAssistants’ Pay Equity claims that have lead to fairer rates of remuneration and abetter understanding of the skills and expertise required of school library staff.